Nanophotosensitizers toward advanced photodynamic therapy of Cancer - Lim, Chang-Keun; Heo, Jeongyun; Shin, Seunghoon; Jeong, Keunsoo; Seo, Young Hun; Jang, Woo-Dong; Park, Chong Rae; Park, Soo Young; Kim, Sehoon; Kwon, Ick Chan (ELSEVIER IRELAND LTD, 2013)
Photodynamic therapy (PDT) is a non-invasive treatment modality for selective destruction of cancer and other diseases and involves the colocalization of light, oxygen, and a photosensitizer (PS) to achieve photocytotoxicity. Although this therapeutic method has considerably improved the quality of life and life expectancy of cancer patients, further advances in selectivity and therapeutic efficacy are required to overcome numerous side effects related to classical PDT. The application of nanoscale photosensitizers (NPSs) comprising molecular PSs and nanocarriers with or without other biological/photophysical functions is a promising approach for improving PDT. In this review, we focus on four nanomedical approaches for advanced PDT: (1) nanocarriers for targeted delivery of PS, (2) introduction of active targeting moieties for disease-specific PDT, (3) stimulus-responsive NPSs for selective PDT, and (4) photophysical improvements in NPS for enhanced PDT efficacy. (C) 2012 Elsevier Ireland Ltd. All rights reserved.
Keywords: ORGANICALLY MODIFIED SILICA; SINGLET OXYGEN GENERATION; 2-PHOTON PHOTOSENSITIZED PRODUCTION; IN-VITRO; ENERGY-TRANSFER; VASCULAR-PERMEABILITY; RADIATION-THERAPY; MOLECULAR BEACON; BLOCK-COPOLYMER; DRUG-DELIVERY